Energy transfer of Tb3+→Eu3+ in Ca2Al2SiO7 phosphors with multicolor tunable and optical temperature sensing properties. (1st May 2023) - Deng, Jiaming; Wang, Zihao; Zhou, Weiping; Yu, Mingyuan; Min, Jiangen; Jiang, Xunliang; Xue, Ziyan; Ma, Chunlin; Cheng, Zhenzhi; Luo, Guangsheng
Abstract: Luminescent temperature sensors based on photoluminescent materials have received considerable attention for their advantages of quick and noninvasive measurement. In this paper, a series of Tb 3+, Eu 3+ single-doped and co-doped Ca2 Al2 SiO7 (CAS) phosphors were synthesized by sol-gel method. The phase purity, surface morphology, energy transfer, luminescence characteristics and temperature sensing properties of Tb 3+, Eu 3+ doped CAS phosphors have been studied carefully. Due to the energy transfer of Tb 3+ →Eu 3+, CAS: Tb 3+, Eu 3+ phosphors demonstrate tunable luminescence under 238 nm excitation, in which the luminescence color gradually changes from purple-red to cool white, and then to warm white by continuously increasing the concentration of Tb 3+ ions. The elongation of the fluorescence lifetime of Eu 3+ with increasing Tb 3+ ions content further confirms the energy transfer of Tb 3+ →Eu 3+ . The thermal behavior of CAS: Tb 3+, Eu 3+ phosphors shows enhanced luminescence intensity for 404 nm emission while suppressed luminescence intensity for 616 nm emissions with raising temperature, implying its potential in optical temperature sensing. Therefore, the temperature sensing performance is evaluated by using the fluorescence intensity ratio ( I 404 nm /I 616 nm ) in CAS: Tb 3+, Eu 3+ phosphors, showing a maximum relative sensitivity of 1.17%K −1 at 443 K. These results indicate that CAS: Tb 3+, Eu 3+ phosphors are promising candidates for tunable luminescence and non-contact temperature sensing.